The transmission mechanism of 2008 global financial crisis to Tehran Stock Exchange - Seyed Gholamreza Jalali Naini; Ahmad Makui; Ehsan Mohebi (Management Science Letters)
After financial crisis in 2008, the effect of crisis spread in the world. Many countries were affected quickly and others slowed in a particular mechanism. Using data of TEPIX from Tehran Stock Exchange and DJI from New York stock Exchange as the main indexes of these two markets, this paper reported strong evidence of TEPIX’s dependency on DJI after the crisis in a four-week delay. The index level series were non-stationary; therefore, we employed cointegration analysis and error correction vector autoregressions (VAR) techniques to model the interdependencies. To find the best lag time we used a heuristic method and the results surprisingly were the same as the result of applying a VAR model. The results support the hypothesis that financial stress was transmitted from the U.S to Iran primarily through trade and price channels.